SUSTAINABLE BUSINESS PRACTICES AND COMMERCE: PATHWAYS FOR ECONOMIC GROWTH AND ENVIRONMENTAL RESPONSIBILITY - L, Ramesh; B, Shiva Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The transition toward sustainable business practices is increasingly becoming a priority as companies adapt to environmental, social, and governance (ESG) mandates. This article explores how sustainable business practices can support economic growth while addressing environmental concerns, with a specific focus on the commerce sector. Analyzing trends, challenges, and benefits, the paper identifies effective strategies for sustainability, concentrating on industries in Chitradurga and neighboring regions in Karnataka. The study highlights global best practices alongside local initiatives, assessing the role of stakeholders, and concludes with actionable recommendations to foster a sustainable and profitable commerce sector.